Mitigating the Effects of Armed Banditry on Poverty: Policy Strategies for Sustainable Development in the North-West Region of Nigeria - Sadiq, Mohammed; Ahmad, Muhammad; Singh, Invinder; Sani, Bashir (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2025)
Armed banditry has become a major threat to socioeconomic stability in Nigeria, particularly in the North-West region, where rural communities are increasingly vulnerable to multidimensional poverty. This study examines the impact of armed banditry on poverty incidence, intensity, and inequality, focusing on the Katsina, Sokoto, and Zamfara States before and after the crisis. Further, using an easy-cost approach, cross-sectional data were collected with the aid of a well-structured questionnaire coupled with an interview schedule from a total of 354 affected households selected through a multi-stage sampling technique. Data collection lasted for a period of three months (October-December) in the year 2024. Using a multidimensional poverty framework, the findings reveal a sharp rise in poverty levels in Katsina and Zamfara States, while Sokoto State experienced a decline, likely due to effective social safety interventions. Rural areas, which rely heavily on agriculture and informal economies, have been particularly affected, with livelihood disruptions, forced displacement, and limited access to education and healthcare exacerbating deprivation. The study further highlights regional disparities, showing that while Katsina and Zamfara bore a disproportionate poverty burden before the attacks, Sokoto experienced this burden post-crisis. Despite the decline in inequality, poverty deepened in rural areas, emphasising the need for targeted interventions to address both security challenges and economic vulnerability. The study recommends strengthening social protection programs, enhancing rural security, promoting economic empowerment, and improving access to education and healthcare. These measures are critical for mitigating poverty, restoring rural livelihoods, and fostering sustainable development in conflict-affected regions.